2004
DOI: 10.1038/sj.ijo.0802700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on asthma among adult Indian women

Abstract: OBJECTIVE: Both obesity and asthma are on the rise worldwide. This study examined the association between obesity and asthma prevalence in adult women in India. METHODS: The analysis used information on 82 464 nonpregnant, ever-married women aged 15À49 y, included in India's 1998À99 National Family Health Survey. The effects of measured Body Mass Index (BMI) on reported asthma were estimated using logistic regression, after adjusting for tobacco smoking (active and passive), cooking smoke, age, education, work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 51 publications
3
45
0
1
Order By: Relevance
“…Weight was measured by using a solar-powered scale with an accuracy of ±100 g, and height was measured with an adjustable wooden measuring board that is designed to provide accurate measurements (to the nearest 0.1 cm) in the context of a developing-country field situation (Mishra 2004 …”
Section: Main Outcome Measurementioning
confidence: 99%
“…Weight was measured by using a solar-powered scale with an accuracy of ±100 g, and height was measured with an adjustable wooden measuring board that is designed to provide accurate measurements (to the nearest 0.1 cm) in the context of a developing-country field situation (Mishra 2004 …”
Section: Main Outcome Measurementioning
confidence: 99%
“…Among people without asthma, age-adjusted mean body mass index increased from 25.4 kg/ m2 in NHANES I to 26.6kg/m2 in NHANES III, and the prevalence of obesity increased from 14.6 to 22.8%. In another study, Mishra et al (14) found a strong positive association between obesity and asthma prevalence in 82464 non-pregnant adult women in India.…”
Section: Discussionmentioning
confidence: 99%
“…비만도가 높아질수록 천식의 유병률이 증가한다는 연구도 세계 각 국에서 많이 보고되고 있다 [8][9][10] . 최근에는 체질량지수 (BMI)와 천식과의 관계에 대한 연구들도 많이 이루어지고 있다 [11][12][13][14][15] .…”
Section: Original Articleunclassified